A Hydrophobic Ionic Liquid Compartmentalized Sampling/Labelling and Its Separation Techniques in Polydimethylsiloxane Microchip Capillary Electrophoresis. (2017) - Quan, H.H.; Li, M.; Huang, Y.; Hahn, J.-H.
Abstract: This paper demonstrated a novel compartmentalized sampling/labelling method and its separation techniques using a hydrophobic ionic liquid (IL) – 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)-imidate (BmimNTf2) as immiscible phase, which is capable of minimizing signal losses during microchip capillary electrophoresis (MCE). The MCE device consists of a silica tube connecting to a straight polydimethylsiloxane (PDMS) separation channel. Poly(diallyldimethylammonium chloride) (PDDAC) was coated on the inner surface of channel for easing the introduction of IL plugs, and enhancing the IL wetting on the PDMS surface for realizing sample releasing. Electroosmotic flow (EOF)-based sample compartmentalization was carried out in a sequenced injection manner by order of leading IL plug/sample segment/terminal IL plug into sampling tube. The moving of the sample segment was easily controlled by applying electrical voltage across both end of the chip without sample volume change. This approach effectively prevented analytes diffusion before the injection into MCE channel. When the sample segment was manipulated to the PDDAC modified PDMS channel, the sample plug then was released from isolation under EOF while IL plugs adsorbed onto channel surface owing to strong adhesion. A mixture of flavin adenine nucleotide (FAD) and flavin mononucleotide (FMN) was successfully separated on a 2.5-cm-long separation channel, for which the theoretical number of plates was 15, 000 and 17, 000, respectively. The obtained peak intensity was increased by 6.3-folds compared to the corresponding value from conventional electrokinetic injection with same sampling time. Furthermore, based on the compartmented sample segment served as an interim reactor, an on-chip fluorescence labelling is demonstrated.